Rapid Prototyping Methodology of Lightweight Electronic Drivers for Smart Home Appliances - Trio Adiono; Rachmad Vidya Wicaksana Putra; Maulana Yusuf Fathany; Braham Lawas Lawu; Khilda Afifah; Muhammad Husni Santriaji; Syifaul Fuada (Institute of Advanced Engineering and Science, 2016)
Many researches have been conducted in smart home topic. Mostly, they discussed on the specific aspect of application. On the other side, many applications still can be explored and attached into the system. Several main challenges in designing the application devices are system complexity, reliability, user friendliness, portability, and low power consumption. Thus, design of electronic driver is one of the key elements for overcoming these challenges. Moreover, the drivers have to comply the rules of smart home system, data protocol, and application purpose. Hence, we propose a rapid prototyping methodology on designing lightweight electronic drivers for smart home appliances. This methodology consists of three main aspects, namely smart home system understanding, circuitry concept, and programming concept. By using this method, functional and lightweight drivers can be achieved quickly without major changes and modifications in home electrical system. They can be remotely controlled and monitored anytime and from anywhere. For prototyping, we design several drivers to represent common electronic and mechanical based applications. Experimental results prove that the proposed design methodology can achieve the research target.